Properties and corrosion behaviors of mild steel in biodiesel-diesel blends. Issue 2 (1st June 2023) - Dharma, S.; Silitonga, A.S.; Shamsuddin, A.H.; Sebayang, A. H.; Milano, Jassinnee; Sebayang, R.; Sarjianto,; Ibrahim, H.; Bahri, N.; Ginting, B.; Damanik, N.
ABSTRACT: Global warming in relation to fossil fuel pollution and their environmental impacts have become a major global concern. Biodiesel has entered the scene as an alternative fuel but it also generated controversy associated with increased residual fuel, increased acidity, oxidation, and corrosion. The main objective of this study was to observe the corrosion behavior of the mild steel immersed in J50C50 biodiesel-diesel fuel blends for up to 800 h at ambient temperature. The results showed corrosion rate at 800-h immersion are 0.0103, 0.0044, 0.0117, 0.0155, 0.2283 and 0.02524 mm/year, respectively, for B0, B10, B20, B30, B40 and B50. Mild steel coupon surface observation using SEM showed corrosion attacks are characterized by round holes on the metal surface. The addition of J50C50 biodiesel into diesel fuel accelerated the corrosion rate and acid value. Overall, corrosion observations conducted on mild steel suggested J50C50 biodiesel-diesel fuel blend is more corrosive compared with diesel fuel.